2017
DOI: 10.1016/j.bbi.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

An examination of changes in maternal neuroimmune function during pregnancy and the postpartum period

Abstract: There is strong evidence that the immune system changes dramatically during pregnancy in order to prevent the developing fetus from being "attacked" by the maternal immune system. Due to these alterations in peripheral immune function, many women that suffer from autoimmune disorders actually find significant relief from their symptoms throughout pregnancy; however, these changes can also leave the mother more susceptible to infections that would otherwise be mitigated by the inflammatory response (Robinson an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 61 publications
3
42
0
1
Order By: Relevance
“…In late pregnancy, there is a reduction in the number of microglia in the brain, specifically in the medial prefrontal cortex, nucleus accumbens, basolateral amygdala and dorsal hippocampus, which seems to be a result of reduced proliferation, rather than increased apoptosis (Haim et al, 2017). In accordance, neuroimmune responses of the maternal brain to immune/inflammatory challenge are suppressed, especially in late pregnancy (Sherer et al, 2017). For example, up-regulation in gene expression for the cytokines, IL-1β and IL-6 in response to bacterial endotoxin LPS administration is markedly attenuated in the prefrontal cortex, preoptic area, hypothalamus and hippocampus of late pregnant rats, compared with non-pregnant females (Sherer et al, 2017).…”
Section: Neuroimmunological Changes In Pregnancymentioning
confidence: 96%
“…In late pregnancy, there is a reduction in the number of microglia in the brain, specifically in the medial prefrontal cortex, nucleus accumbens, basolateral amygdala and dorsal hippocampus, which seems to be a result of reduced proliferation, rather than increased apoptosis (Haim et al, 2017). In accordance, neuroimmune responses of the maternal brain to immune/inflammatory challenge are suppressed, especially in late pregnancy (Sherer et al, 2017). For example, up-regulation in gene expression for the cytokines, IL-1β and IL-6 in response to bacterial endotoxin LPS administration is markedly attenuated in the prefrontal cortex, preoptic area, hypothalamus and hippocampus of late pregnant rats, compared with non-pregnant females (Sherer et al, 2017).…”
Section: Neuroimmunological Changes In Pregnancymentioning
confidence: 96%
“…Alternations in microglia, the brain's innate immune cells, have been detected in female rats, with a significant reduction in microglial density and count during late pregnancy and early postpartum in the amygdala, medial prefrontal cortex, nucleus accumbens, and hippocampus [50], indicating a central role of neuroimmune mechanisms in maternal brain plasticity. Hippocampal concentrations of the cytokines interleukin (IL)-6 and IL-10 have been shown to increase in rats after parturition [50], and distinct changes in IL-6 and IL-1β expression have been observed in the hippocampus and medial prefrontal cortex during pregnancy and postpartum [51].…”
Section: Neural Adaptationsmentioning
confidence: 99%
“…Further, the postpartum period has been characterized by elevated cytokine levels and high infiltration of immune cells (Shynlova, Nedd‐Roderique, Li, Dorogin, & Lye, ; Yoshii, Kitahara, Ueta, Matsuno, & Ezaki, ). Contradictory to the increased peripheral activity reported in the postpartum period, studies in rodents have indicated a decreased number of microglial cells in the brain and a suppression of the cytokine response in the maternal brain during late pregnancy and early postpartum (Haim et al, ; Posillico & Schwarz, ; Sherer, Posillico, & Schwarz, ).…”
Section: Introductionmentioning
confidence: 99%